Estimating the Cost of Capital Through Time: An Analysis of the Sources of Error - Ferson, Wayne E.; Locke, Dennis H. (Management Science, 1998)
Practitioners needing estimates of a firm's equity cost of capital have long relied on the Capital Asset Pricing Model (CAPM). Recent evidence casts renewed doubt on the validity of the CAPM and beta. However, there is not much evidence to gauge the importance of the rejections of the CAPM in a practical decision-making context. This paper presents evidence on the sources of error in estimating required returns over time. We use a number of proxies for the true mean variance efficient portfolio, allowing that the CAPM is the “wrong” model. The analyst is assumed to rely on a standard market index. We find that the great majority of the error in estimating the cost of equity capital is found in the risk premium estimate, and relatively small errors are due to the risk measure, or beta. This suggests that analysts should improve estimation procedures for market risk premiums, which are commonly based on historical averages. This can be done by using regression models, such as have appeared in the recent finance literature, or by purchasing forecasts from firms that specialize in producing them.